The association between insulin resistance and hepatic fibrosis in patients with chronic hepatitis C: An observational, multicenter study in Turkey - Dökmeci, Abdulkadir; Üstündağ, Yücel; Hulagu, Saadettin; Tuncer, İlyas; Akdoğan, Meral; Demirsoy, Hüseyin; Köklü, Seyfettin; Güzelbulut, Fatih; Doğan, İbrahim; Demir, Ali; Akarsu, Mesut; Yüceyar, Hakan; et al. (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: To evaluate the association between insulin resistance and hepatic fibrosis in patients with chronic hepatitis C. Materials and Methods: A total of 104 chronic hepatitis C patients were included in this non-interventional, open-label, observational, multicenter, cross-sectional study conducted at 20 gastroenterology clinics in Turkey. The primary end point was the correlation between stage of hepatic fibrosis and insulin resistance evaluated via the homeostasis model of assessment-insulin resistance index. Confounders of hepatic fibrosis and insulin resistance were the secondary end points. Results: The mean age of patients was 52.8 years; 65.4% were female. Type 2 diabetes was present in 6.8% and insulin resistance noted in 38.0% of patients. Further, 45.7% of the patients had mild (A0/A1) and the remaining had moderate/severe (A2/A3) hepatic necroinflammatory activity. Patient distribution according to Metavir fibrosis stage was as follows: F0/F1 (57.0%); F2 (6.5%); F3 (23.7%); and F4 (12.9%). A univariate analysis revealed significant positive correlations between Metavir fibrosis stage and insulin resistance (r=0.297; p=0.007). Logistic regression analysis showed that significant predictors of insulin resistance were high alanine transaminase levels (odds ratio, 0.97; 95% confidence interval, 0.944-0.997) and liver fibrosis stage (odds ratio, 0.114; 95% confidence interval, 0.021-0.607). Conclusion: Our findings revealed significant associations between insulin resistance and hepatic fibrosis.